Aging - Challenges of the XXI Century - Quaresma, Maria de Lourdes Baptista (2016)
The relationship between social development, longevity increase and historical time is our object of analysis. Stretching adulthood, new social risks and the consequent need to adapt social policies in a historic time of profound change, guides the reflection on the future and role of different social actors in building the right to age with dignity and security, which is a link that unites different generations.Keywords: Longevity; Social development; Social policies.